A Screening Test for HLA-B∗15:02 in a Large United States Patient Cohort Identifies Broader Risk of Carbamazepine-Induced Adverse Events - Hua Fang; Xiequn Xu; Kulvinder Kaur; Matthew Dedek; Guang-dan Zhu; Bae J. Riley; Frank G. Espin; Andria L. Del Tredici; Tanya A. Moreno (Frontiers Media S.A., 2019)
Purpose:HLA-B∗15:02 is strongly associated with life-threatening severe skin hypersensitivity reactions in patients treated with carbamazepine (CBZ) and structurally related medications. FDA-approved labeling recommends HLA-B∗15:02 screening before CBZ therapy in patients of Asian ancestry. In this study, we aimed to (a) identify a direct method for screening HLA-B∗15:02, and (b) evaluate prevalence in a large cohort of United States patients.Methods: Candidate genetic markers were identified by mining public data. Association was tested in 28,897 individuals by comparing SNP results with high-resolution HLA typing. Retrospective analysis of de-identified SNP and ethnicity data from 130,460 individuals was performed to evaluate the ethnic distribution of HLA-B∗15:02 in the United States.Results: 28,897 United States individuals showed 100% concordance between HLA-B∗15:02 and the minor allele of rs144012689 (100% sensitivity/99.97% specificity). Retrospective analysis of 160 positive individuals (66 with physician-reported ethnicity) notably included 28 Asians (42%), 15 African Americans (22%), 11 Caucasians (17%), 2 Hispanics (3%), and 10 "Other" (15%).Conclusion: Screening United States patients for HLA-B∗15:02 without ethnicity-based preselection identifies more than twice the number of carriers at risk of CBZ-related adverse events than screening patients of Asian ancestry alone. Risk assessment based on ethnicity assumptions may not identify a large portion of at-risk patients in the ethnically diverse United States population.